Lattice Boltzmann simulation for phase separation with chemical reaction controlled by ultrasound field. - Heping Wang; Ying Lu (PLoS ONE)
In this work, the phase separation behavior and pattern formation in binary fluids with chemical reactions controlled by ultrasonic radiation were systematically investigated. We incorporated the density-dependent Arrhenius equation into a novel and modified model for phase separation. The coupling effects of the pre-exponential factor K, density, and frequency on the phase separation under the condition of ultrasonic field-regulated chemical reactions were evaluated. 1) The rate of chemical reaction can be slowed down and even blocked by controlling the frequency of the ultrasonic field. 2)We have established a criterion for evaluating the competition between chemical reactions and the ultrasonic fields. When the value of pre-exponential factor K is greater than or equal to 10-4, phase separation is primarily regulated by the chemical reaction; otherwise, the ultrasonic field dominates the phase separation. 3) By analyzing the average structure factor, it was quantitatively proven that an increase in the frequency can significantly shorten the phase preservation period of the chemical reaction and ultrasonic radiation force and accelerate the merging of the separated phases into a larger phase. 4) We have successfully simulated the morphological evolution of phase separation regulated by traveling waves in the ultrasonic field.